A review of mental health policies from Commonwealth countries. (February 2018) - Bhugra, Dinesh; Pathare, Soumitra; Joshi, Rajlaxmi; Kalra, Gurvinder; Torales, Julio; Ventriglio, Antonio
Background: The burden of disease related to mental disorders across the world is substantial. However, there remains inequality between funding for clinical and research activities between physical illness and mental illness in almost all countries. Aims: One way of reducing this inequality is to ensure that mental health policies reflect this. We were interested in looking at the policies of members of Commonwealth. Method: We decided to survey 52 member countries of the Commonwealth to explore whether mental health policies existed and whether there was equity between physical and mental health services funding. Using World Health Organization (WHO) data sets and other sources when indicated, we looked at the existence and contents of mental health policies. Results: We found that less than half of the countries had a mental health policy. Deinstitutionalization was not seen as a priority in many countries and there was no equity between physical and mental health funding. Although integration between physical and mental health care was recommended in many countries, there was a clear gap. Conclusion: It is apparent that there is still a long way to go in terms of equity between physical and mental health in terms of funding in member states of the Commonwealth. These findings confirm earlier observations of discrimination against people with mental illness. We suggest that there must be mechanisms in place to facilitate and support change wherever required.